The digitalize of car manual book for Perodua Myvi / Muhamad Sahli Azhar - Azhar, Muhamad Sahli (Faculty of Art and Design, 2015)
This study will investigate the use of the car manual book among users of Perodua Myvi. Motor vehicle driving has been changing over time and is still changing. Much more driving is done by today than in the past. Everyone are driving and they are driving more miles.Therefore they did not escape from car breakdown while driving. The lack in term of reading manual books will be negative impact to the drivers. An owner's manual (also called an instruction manual) is an instructional book or booklet that is supplied with almost all technologically advanced consumer products such as vehicles, home appliances and computer peripherals. ( Mischel, 1991 ). Until the last decade or two of the twentieth century it was common for an owner's manual to include detailed repair information. Moreover, They lack in terms of reading information and also maintenance. Indirectly, it will be a negative impact to the drivers. Thus, with the increasing complexity of modern devices,many owner's manuals have become so large that a separate quickstart guide is provided.